CCS02.1 Dequalinium chloride vaginal tablets for recalcitrant trichomonas vaginalis (TV): a case report. (14th July 2019) - Goode, Deborah; Astill, Natasha; Wilson, Janet
Abstract : Background: Treatment for TV is often ineffective. Even very high-dose tinidazole has 8–10% failure and subsequent treatment options have limited evidence-base. Dequalinium has an EU license for bacterial vaginosis treatment. It is well tolerated, safe and has in-vitro activity against TV, but clinical experience is limited. We present the case of an 18-year old female with a 12-month history of persistent TV despite standard and resistant treatments, which finally responded to prolonged dequalinium. Methods: The patient was white British with no significant medical history. The presumed source of infection was a male living in Dubai. There was no risk of reinfection and adherence was self-reported as excellent throughout. Initial and subsequent presentations were with typical symptoms of vulvovaginitis and purulent vaginal discharge. Investigations were with onsite microscopy and TV nucleic acid amplification tests (NAAT). Treatment initially followed the British Association of Sexual Health and HIV TV Guideline. She received: several courses of 7-day and very high dose oral metronidazole (once with concurrent ampicillin and clotrimazole pessaries); intravenous metronidazole administered alongside vaginal metronidazole gel; oral tinidazole with intravaginal metronidazole. All nitroimidazole courses were up to 14 days duration. Vulvovaginitis symptoms settled during antimicrobial therapy, but recurred soon after cessation of treatment. At each follow-up TV was confirmed by microscopy and NAAT. We retreated with 4-weeks of metronidazole 400 mg twice daily with dequalinium intravaginal pessaries nightly. Symptoms were controlled, but TV NAAT and microscopy remained positive. As there was symptomatic relief from dequalinium, this was continued as monotherapy for a further 14 weeks pending sourcing alternative treatments. Results: Her symptoms remained controlled and microscopy and NAAT became negative. She remained asymptomatic with negative microscopy and NAAT 2 months after stopping dequalinium. Conclusion: Prolonged dequalinium may offer an alternative treatment option for recalcitrant TV, particularly where high dose systemic antibiotics have been unsuccessful. Disclosure: No significant relationships.